RIADENIE DOPRAVY AKO PROSTRIEDOK PROTI VZNIKU KRIZOVÝCH SITUÁCIÍ (Perner's Contacts, 2007)
In Slovak condition is managing of transportation one of the possible tools for solving potential crisis situations. The article describes about possibility of using intelligent transport systems and their tasks in transport system.
Keywords: Crisis situation; integrated transport system; managing of transportation